A Comparative Study and Numerical Solutions for the Fractional Modified Lorenz–Stenflo System Using Two Methods - Mohamed Elbadri; Mohamed A. Abdoon; Abdulrahman B. M. Alzahrani; Rania Saadeh; Mohammed Berir (Axioms)
This paper provides a solution to the new fractional-order Lorenz–Stenflo model using the adaptive predictor–corrector approach and the <semantics>ρ</semantics>-Laplace New Iterative Method (<semantics>LρNIM</semantics>), representing an extensive comparison between both techniques with RK4 related to accuracy and error analysis. The results show that the suggested approaches allow one to be more accurate in analyzing the dynamics of the system. These techniques also produce results that are comparable to the results of other approximate techniques. The techniques can, thus, be used on a wider class of systems in order to provide more accurate results. These techniques also appropriately identify chaotic attractors in the system. These techniques can be applied to solve various numerical problems arising in science and engineering in the future.